Isolation, Identification of Pectobacterium Bacteria Causing Soft Rot on potato Plant in Al Bayda - Aljabal Alakhdar - Bofarwa, Hosnia (Scientific Journal for Faculty of Science-Sirte University, 2024)
This study aimed to isolate and diagnose the bacteria causing soft rot disease on Potatoes in some markets in the city of Al-Bayda, testing their pathogenicity, as well as testing their sensitivity to some antibiotics and biochemical tests. A bacterial isolate was obtained from tubers infected with soft rot disease and from all samples collected from some fields and stores in the markets of the city of Al-Bayda. The pathogenicity test on potato slices proved that the bacterial isolate was capable of causing the disease. The results of phenotypic and biochemical tests showed that the bacteria were Pectobacterium. A test showed sensitivity to some antibiotics. The results of this study showed that all tested antibiotics are toxic Against Pectobacterium, but to varying degrees, except for the antibiotic Tetracyclin But to varying degrees, the antibiotic was Erythromycine One of the most effective antibiotics, as it blocks the biosynthesis of Erythromycine Bacteria grow in an area with an average diameter of 3 cm They came with the antibiotic Amoxicilline It ranked second in terms of effectiveness, as the diameter of the area free of bacterial growth around the disc containing it reached an average of 1.5 cm, and the antibiotic Tetracyclin did not show any toxic effect on the bacteria. that The tested antibiotics differed in their effects Where the antibiotic Erythromycine was on the bacteria Highly effective while the antibiotic Amoxicilline was The effect was moderate, while the antibiotic Tetracyclin was Ineffective. This difference may be due to the fact that the tested antibiotics may They differ in their interaction with components of the bacterial cell wall or their contents. .